1976
DOI: 10.2466/pr0.1976.38.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Structure of the Death Concern Scale

Abstract: Dickstein's (1972) 30-item Death Concern Scale was developed as a measure of the extent to which an individual consciously contemplates death and evaluates it negatively. Scoring procedures provide a single score as a measure of death concern. Dickstein's definition of death concern and an examination of the items support the authors' contention that two aspects of death concern are being measured. Factor analyses of the item scores of 671 college students indicated the presence of two distinct factors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 3 publications
0
15
1
Order By: Relevance
“…41,42 Other studies have also reported reliabilities around 0.80. 17,43,44 The correlation between two parts of the DCS was strong and positive (r=0.72),…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…41,42 Other studies have also reported reliabilities around 0.80. 17,43,44 The correlation between two parts of the DCS was strong and positive (r=0.72),…”
Section: Methodsmentioning
confidence: 99%
“…5 Scores on the DCS are moderately correlated with scores on the DAS, ranging from 0.40 to 0.60. 5,45 Factor analyses of the DCS have identified from one single factor to nine factors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these are physiological and psychological nearness to death {Feifel, 1961;Feifel and Branscomb, 1973), recent experience with death (Feifel and Branscomb, 1973;Kastenbaum and Costa, ·1977), the meaning of death· to the individual such as death of self versus death of another and the act of dying versus the state .of death- (Lester, l967a;Kastenbaum and Aisenberg, 1972;Feifel and Branscomb, 1973;Klug and Boss, 1976). …”
mentioning
confidence: 99%